Efficacy of Oral Chemolytic Dissolution for Uric Acid and Cystine Urolithiasis: A Systematic Review and Meta-Analysis of Contemporary Primary Evidence - Muhammad Bintang Iqbal; Jufriady Ismy (Open Access Indonesian Journal of Medical Reviews, 2025)
Uric acid (UA) and cystine urolithiasis pose unique treatment challenges due to their metabolic origin and high recurrence rates. Oral chemolysis, which targets their underlying pathophysiology, is an alternative to surgical intervention. This study aims to provide a quantitative synthesis of its dissolution efficacy and impact on recurrence based on contemporary primary data. Following PRISMA guidelines, we systematically searched PubMed, Scopus, and the Cochrane Library from January 2015 to October 2025. We included randomized controlled trials (RCTs) and observational studies evaluating oral chemolysis (alkalizing agents for UA; thiol-based agents for cystine) in adults. Primary outcomes (complete stone dissolution) and secondary outcomes (recurrence) were pooled using a random-effects model with Restricted Maximum Likelihood (REML) estimation. Nine primary studies involving 812 patients met the inclusion criteria. For uric acid stones (6 studies, n=597), the pooled proportion of complete dissolution was 69.2% (95% CI: 62.1% - 76.3%; I²=48%). Continuous alkalization therapy was associated with a 66% reduction in 2-year recurrence (Risk Ratio [RR] 0.34; 95% CI: 0.23 - 0.50). For cystine stones (3 studies, n=215), the pooled dissolution rate based on a small cohort was 33.1% (95% CI: 25.0% - 41.2%; I²=29%). Thiol-based therapy was associated with a 40% reduction in 2-year recurrence (RR 0.60; 95% CI: 0.41 - 0.88). In conclusion, oral alkalization is a highly effective primary therapy for appropriately selected patients with uric acid stones. For the more recalcitrant cystine stones, dissolution efficacy is modest and based on limited data, positioning chemolysis as a critical adjunctive therapy. These findings reinforce clinical guideline recommendations for a pathophysiology-based medical approach in non-obstructing metabolic stones.